ICT Investments and Firm Productivity: An Analysis Using Micro Data - TAKIZAWA, Miho; MIYAKAWA, Daisuke (THE KEIZAI BUNSEKI (THE ECONOMIC ANALYSIS), 2024)
This paper empirically examines the causal effects of ICT investments on firm employment and productivity. Based on an identification strategy using the survey responses of firms about the impact of the tax benefit on their ICT investments, we find the following: The increase in ICT investments responding to the tax benefit resulted in the conversion of internal non-ICT labor to ICT labor. Second, such conversion did not improve labor productivity. These results suggest that additional investments such as the investment on the quality of ICT labor (e.g., ICT literacy) is necessary for ICT investments to improve firm productivity.